Comparative evaluation of midazolam, dexmedetomidine, and propofol as Intensive Care Unit sedatives in postoperative electively ventilated eclamptic patients - Malik Rameez Rashid; Rukhsana Najeeb; Saima Mushtaq; Rizwana Habib (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Eclampsia is a common hypertensive disorder of pregnancy and treatment often includes termination of pregnancy with elective postoperative mechanical ventilation. The present study was aimed to compare midazolam, propofol, and dexmedetomidine for sedation and antihypertensive requirements of such patients admitted to Intensive Care Unit (ICU) after termination of pregnancy. Material and Methods: A total of ninety eclamptic patients administered general anesthesia for the termination of pregnancy through cesarean section and who also required postoperative ventilation were taken up for the study and were randomly allocated into three groups. All patients received MgSO4 (loading dose, 4 g intravenous) following first seizure episode followed by a continuous infusion for next 24 h. Midazolam group (GrM) received 0.05 mg/kg loading dose of midazolam, followed by infusion of 0.05-0.3 mg/kg/h, propofol group (GrP) received 1 mg/kg loading dose of propofol followed by infusion of 2-8 mg/kg/h, and dexmedetomidine group (GrD) received dexmedetomidine loading dose at 1 mcg/kg followed by infusion of 0.2-1.2 mcg/kg/h. Postoperatively, patients were assessed for hemodynamic stability, requirement of antihypertensive and analgesics, duration of sedation and stop sedation-discharge, and total time spent in the ICU. Results: Mean heart rate and mean arterial pressure recorded at different time intervals were lowest in GrD. Nearly 70% (n = 21) patients in the GrM required antihypertensive, 50% (n = 15) in GrP, and 36.6% (n = 11) in the GrD (P < 0.05). Duration of stop sedation-discharge from ICU was least in GrD. A number of patients demanding additional analgesics was also least in GrD. Conclusion: Sedation with dexmedetomidine produced better hemodynamic stability in eclamptic patients, and there was a significant reduction in requirement of additional analgesics (P = 0.035) and antihypertensive (P = 0.004). Total duration of ICU stay was also less in this group of patients.